Penilaian Parut Hipertrofi Luka Bakar Berdasarkan Patient and Observer Scar Assessment Scales (POSAS) - Eko S. Sinaga; Mendy Hatibie; Maximillian C. Oley; Fredrik G. Langi (Universitas Sam Ratulangi, 2024)
Abstract: Hypertrophic scar of burn can occur due to the imbalances in the wound healing process that can affect the quality of life. Patient and Observer Scar assessment Scales (POSAS) is an assessment instrument both from the patient and the observer. This study aimed to assess hypertrophic scars with POSAS. This was an observational and analytical study with a cross sectional design. Samples were patient with burns admitted to Prof. Dr. R. D. Kandou Hospital, Manado, and its network hospitals. The assessment was carried out directly when the patients being admitted to the hospital. Each patient who met the requirements had demographic and clinical data taken. Subsequent assessments were carried out at one month and six months after the initial treatment procedure. The results obtained 30 patients with burn dominated by females (63%). The most common degree of burns was superficial-middermal (67%). The assessment of POSAS by doctors and patients tended to be the same and both decreased in the first month and the sixth month after initial treatment procedure with a mean value of the total pre- initial treatment procedure score of 51.3±12.1; 1st month 44.2±9.5; 6th month 30.3±5.9. In conclusion, the evaluation of burns that produce acceptable hypertrophic scars using the POSAS score shows similarities in the assessment of observers and patients. Moreover, precautions at the beginning of the observation will affect the POSAS score Keywords: burn; hypertrophic scar; Patient and Observer Scar Assessment Scales Abstrak: Parut hipertrofi paska luka bakar dapat terjadi karena ketidakseimbangan pada proses penyembuhan luka yang dapat memengaruhi kualitas hidup. Patient and Observer Scar Assessment Scales (POSAS) merupakan instrumen penilaian parut baik dari pasien maupun observer. Penelitian ini bertujuan untuk menilai parut hipertrofi dengan menggunakan POSAS. Jenis penelitian ialah observasional analitik dengan desain potong lintang. Sampel penelitian ialah pasien dengan luka bakar yang dirawat di RSUP Prof. Dr. R. D. Kandou dan rumah sakit jejaring. Penilaian dilakukan langsung saat pasien masuk rumah sakit. Setiap pasien yang memenuhi persyaratan diambil data demografik dan kliniknya. Penilaian selanjutnya dilakukan pada satu bulan dan enam bulan paska tindakan perawatan awal. Hasil penelitian mendapatkan 30 pasien dengan luka bakar yang didominasi oleh pasien perempuan (63%). Derajat luka bakar terbanyak ialah superficial-middermal (67%). Penilaian POSAS oleh dokter dan pasien cenderung sama dan mengalami penurunan baik pada bulan pertama dan bulan keenam setelah tindakan dengan nilai mean skor total pra tindakan 51,3±12,1; bulan pertama 44,2±9,5; dan bulan keenam 30,3±5,9. Simpulan penelitian ini ialah evaluasi luka bakar yang menghasilkan jaringan parut akseptabel menggunakan skor POSAS menunjukkan kesamaan penilaian menurut observer dan pasien. Tindakan pencegahan pada awal pengamatan akan memengaruhi skor POSAS. Kata kunci: luka bakar; parut hipertrofi; Patient and Observer Scar Assessment Scales